Rendimiento potencial de biocombustibles sólidos del bosque de terraza media de diferentes clases diamétricas y densidades básicas, Puerto Almendra, Iquitos-Perú, 2023 - Pinedo Yañez, Tonny Martin (2025)
The potential yield of solid biofuels from the mid-slope forest of different diameter classes and basic densities within the area of plot "V" of the Arboretum "El Huayo" at CIEFOR - Puerto Almendra was quantified. The calculation to determine the potential yield of biofuels, charred wood, and charcoal was done through strip inventory, taking into account the diameter class of the trees with an interval of 10 cm, and the basic density of the wood is classified as low, medium, high, and very high. According to the average yield obtained in the wood chemistry laboratory of the Faculty of Forestry Sciences, these data have been projected onto the tree inventory to make correct inferences for a larger group of individuals. The highest potential yields of solid biofuels from charred wood were quantified in the diameter classes of 20 cm and 30 cm with 28,326.36 kg and 24,549.09 kg, respectively; and the yield in coal in the same diametric classes with 14,184.77 kg and 11,991.66 kg respectively. Meanwhile, the highest yields in toasted wood were in trees with medium and very high basic density levels with 45,032.65 kg and 31,586.01 kg respectively; and the yield of charcoal in trees with medium and high density levels with 21,192.19 kg and 16,807.21 kg respectively; and the highest potential species are Alchornea triplinervia (Spreng.) Müll. Arg., Caryocar glabrum (Aubl.) Pers. and Bertholletia excelsa Bonpl.